2017
DOI: 10.5539/jas.v9n10p76
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Genetic Resources of Farmed Tambaqui in Northern Brazil

Abstract: The present study analyzed the genetic variability and structure of farmed tambaqui in the Brazilian state of Pará, and provided basic information that can be used for the development of programs of monitoring and management of genetic resources in the aquaculture operations of northern Brazil. A total of 216 individuals were sampled from tambaqui farms in Pará. Genotyping was based on a multiplex set of 10 tri-and tetra-nucleotide microsatellite markers. The data were used to calculate genetic diversity indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Santos et al () utilized isoenzymes to compare tambaqui populations, and they observed low values of H O in the tambaqui fish farms (Northeast and Southeast Brazil) when compared with wild tambaqui of the Amazon basin. Previous studies with neutral genetic markers also indicated loss in the genetic variability in tambaqui fish farms (Aguiar et al, ; Aguiar et al, ; Costa et al, ; Fazzi‐Gomes, Melo et al, ; Jacometo et al, ; Lopes et al, ; Queiroz et al, ; Santos et al, ). The absence of gene flow between fish farms resulted in increased inbreeding, except when there is an improvement in the stock (e.g., NortA fish farm).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Santos et al () utilized isoenzymes to compare tambaqui populations, and they observed low values of H O in the tambaqui fish farms (Northeast and Southeast Brazil) when compared with wild tambaqui of the Amazon basin. Previous studies with neutral genetic markers also indicated loss in the genetic variability in tambaqui fish farms (Aguiar et al, ; Aguiar et al, ; Costa et al, ; Fazzi‐Gomes, Melo et al, ; Jacometo et al, ; Lopes et al, ; Queiroz et al, ; Santos et al, ). The absence of gene flow between fish farms resulted in increased inbreeding, except when there is an improvement in the stock (e.g., NortA fish farm).…”
Section: Discussionmentioning
confidence: 91%
“…In Brazil, fish farms do not present records of animals' origin, pedigree, or genetic information. Furthermore, several studies of genetic variability show loss of gene diversity and signs of inbreeding in the populations of tambaqui from different Brazilian regions (Aguiar et al, ; Aguiar et al, ; Costa, Rodrigues, & Matoso, ; Fazzi‐Gomes et al, ; Jacometo et al, ; Lopes et al, ; Queiroz, Sousa, Silva, & Inoue, ; Santana et al, ; Santos et al, ; Santos, Santana, Sá Leitão, Paula‐Silva, & Almeida‐Val, ). Therefore, it is necessary to estimate the impacts of the selective pressure caused by aquaculture, as well as the management of this genetic resource.…”
Section: Introductionmentioning
confidence: 99%
“…As armadilhas pressupõem, na pesca como na caça, que a presa entre em uma câmara/estrutura que impossibilite ou dificulte sua saída, sendo atraída por iscas ou em busca de abrigo. Na captura de peixes, as armadilhas apresentam a vantagem de causar poucos danos e, em alguns casos, como no uso de covos em ambiente de água doce até de manter os Research, Society and Development, v. 9, n. 8, e516985696, 2020 (CC BY 4 (Fazzi-Gomes, et al, 2017;Santos, et al, 2013;Ramalho, et al, 2012).…”
Section: Resultsunclassified
“…Thus, propagation of this ‘primary farmed type’ (Mair & Lucente 188 ) has been established to produce fingerlings for local tambaqui farming. The genetic diversity of captive populations maintained in public and private hatcheries was assessed using multiple molecular markers, including random amplified polymorphic DNA (RAPD), 192,205,206 mitochondrial DNA, 207‐209 inter‐simple sequence repeat (ISSR), 210 microsatellite 208,211‐215 and SNP 216 markers. Altogether, it was shown that the genetic resources of farmed tambaqui broodstock in the Amazon region and across other South American regions underwent loss of genetic diversity, which can be attributed to the lack of effective breeding management and founder effects resulting from the species’ high fecundity and small number of broodstock utilized.…”
Section: Genetics Genomics and Selective Breedingmentioning
confidence: 99%